New roles for Smad signaling and phosphatidic acid in the regulation of skeletal muscle mass - Goodman, Craig A. (©2014 Faculty of 1000 Ltd, 2014)
Skeletal muscle is essential for normal bodily function and the loss of skeletal muscle (i.e. muscle atrophy/wasting) can have a major impact on mobility, whole-body metabolism, disease resistance, and quality of life. Thus, there is a clear need for the development of therapies that can prevent the loss, or increase, of skeletal muscle mass. However, in order to develop such therapies, we will first have to develop a thorough understanding of the molecular mechanisms that regulate muscle mass. Fortunately, our knowledge is rapidly advancing, and in this review, we will summarize recent studies that have expanded our understanding of the roles that Smad signaling and the synthesis of phosphatidic acid play in the regulation of skeletal muscle mass.